A percepção dos dirigentes de cooperativas agroindustriais do oeste do Paraná quanto a projetos de energia solar e proposta de modelo de análise de viabilidade - Delabeneta, Cibely (2019)
This research aimed to analyze the leaders’ knowledge of agro-industrial cooperatives regarding Solar Energy projects and to propose an analysis model of investment feasibility. The research was classified as descriptive, survey and documentary, with qualitative and quantitative approaches. This study was structured in two phases. During the first one, a questionnaire was applied and answered by 51 leaders of 11 agro-industrial cooperatives. The collected data were processed in the Statistical Package for the Social Sciences software (SPSS), with a data descriptive analysis, followed by cross-section analysis, with data crossing. The results regarding leaders’ perception on solar photovoltaic energy application have predicted that the projects are not feasible for a large consumer plant. However, they have shown a great assumption to insert solar energy in part of the cooperative, especially in the consumer units that do not use the energy that was hired on the free market. The second stage of this study analyzed some investment feasibility for solar energy projects. Deterministic methods of investments evaluation were applied for the risk and return analysis: Net Present Value (NPV), Modified internal rate of return (MIRR), Rate of return (ROR) and Profitability index (PI). During the probabilistic analysis, with @ Risk® tool, for the Monte Carlo simulation, 10,000 iterations of risk and return scenarios were generated for three different levels of projects, with 400KW, 1MW and 5MW power. The results showed that only two projects presented feasibility: 400KW and 1MW, both with energy rate, practiced in the captive market, which were calculated according to the financing of Linha Fundo Clima conditions. The main contributions of this research are: managers' perception headed to the impossibility of solar projects due to the high cost of investments; cooperative leaders’ bias to use solar energy and comply with part of the cooperative consumption; study of return and risk analyses of investment in solar energy projects subsidized by a more robust tool; and the influence of subsidies on both interest rates of financing and energy rate on viability of solar energy projects.